Swelling and Eicosanoid Metabolites Differentially Gate TRPV4 Channels in Retinal Neurons and Glia - Ryskamp, Daniel A. (J Neurosci, 2014)
Activity-dependent shifts in ionic concentrations and water that accompany neuronal and glial activity can generate osmotic forces with biological consequences for brain physiology. Active regulation of osmotic gradients and cellular volume requires volume-sensitive ion channels. In the vertebrate retina, critical support to volume regulation is provided by Müller astroglia, but the identity of their osmosensor is unknown. Here, we identify TRPV4 channels as transducers of mouse Müller cell volume increases into physiological responses. Hypotonic stimuli induced sustained [Ca(2+)](i) elevations that were inhibited by TRPV4 antagonists and absent in TRPV4(−/−) Müller cells. Glial TRPV4 signals were phospholipase A2- and cytochrome P450-dependent, characterized by slow-onset and Ca(2+) waves, and, in excess, were sufficient to induce reactive gliosis. In contrast, neurons responded to TRPV4 agonists and swelling with fast, inactivating Ca(2+) signals that were independent of phospholipase A2. Our results support a model whereby swelling and proinflammatory signals associated with arachidonic acid metabolites differentially gate TRPV4 in retinal neurons and glia, with potentially significant consequences for normal and pathological retinal function.